Note on the denominated contractual liability. False myth or historical category in constant transformation? - Espinoza Espinoza, Juan (2016)
In this article, the author explains the forms, consequences, and exceptions of breach of a contract from the perspective of comparative law. Thus, he aims to understand legal situations, which seek to protect the right of credit, such as the repair of the damages. The author makes distinctions when defining whether the security obligation is part of the contract or not, which allows to distinguish the nature of objectivity or subjective contractual liability.